Antenna for 5G mobile Communications Systems at 10 GHz - Sani Yahya, Muhammad; Abdul Dalyop, Ishaku; Saleh, Yusuf; Aminu-Baba, Murtala (International Journal of Engineering and Technology, 2018)
The design of compact dual band grid array antenna (GAA) designed on FR-4 substrate for future Fifth Generation (5G) Mobile Communications at 10 GHz is reported. The proposed antenna uses coaxial technique of feeding and has a dimension of 48 mm Ã— 55 mm Ã— 1.6 mm. Simulation results using CST microwave studio illustrates that the antenna has a band from 10.03 GHz to 10.68 GHz and another band from 10.7 GHz to 12.23 GHz. This excludes the 10.68 â€“ 10.7 GHz band in which emissions were forbidden by the Radio Regulations in the sense that it has been allocated for the Radio Astronomy, Space Research and Earth Exploration Satellite (passive). The antenna has a maximum gain of 8.03 dBi at 10 GHz, thus a good candidate for the future 5G mobile communications.Â